Validity and reliability of three-dimensional imaging for measuring the volume of the arm - Erends, Maaike; van der Aa, Teike; de Grzymala, Andrzej Piatkowski; van der Hulst, Rene (Lymphatic research and biology, 2014)
Lymphedema of the upper limb is a common complication after cancer treatment with axillary lymph node surgery and/or radiation. At this moment, there is no method that can identify lymphedema error free. Currently three-dimensional (3D) imaging is used to measure volumes in aesthetic and maxillofacial surgery. This study aims to assess the validity and reliability of 3D volume measurements of the upper limb compared with the current gold standard (water displacement method). Thirty-three subjects were included which completed both measurements. The accuracy of the aforementioned methods was compared in a within subject design. The analysis showed a mean difference between the two measurements of -13.8 cc (SD 59.3), this volume difference was not significant (p=0.192). Both the intra- and inter-rater reliability of the 3D measurements were high (0.99). The 3D volume measurements of the arm are valid and reliable. Therefore we recommend the 3D method for measuring arm volumes. Since this method is now validated for arms without lymphedema, we plan to validate this new technique for patients with lymphedema.